Fine Needle Aspiration Cytology In The Diagnosis Of Head And Neck Masses - Khdhayer, Akeel A.; Al-Azawi, Mazin Jasim; Al-Alash, Nawal; Yasseen, Hadeel A. (European Scientific Journal, ESJ, 2016)
Background Commonly presenting neck masses occur within lymph nodes, thyroid, parotid and other salivary glands. Objective This study is designed to assess the accuracy, sensitivity, specificity in various head and neck lesions Material and method fine needle cytology and the histopathology were done on 100 patients who presented with palpable head and neck mass (es). Result Sensitivity, specificity, and accuracy for detection of lymphoma is 50%, 90%, 70.0% respectively. While the overall sensitivity, specificity, accuracy is 88%, 98%, 93%. Conclusion fine needle aspiration is a highly accurate method for primary diagnosis of neck masses apart from lymphoma.